Risk Factors of Mortality In Probable Covid-19 Cases In RSUP Dr. Kariadi Semarang - Prashandika, Yui; Pramudo, Setyo Gundi; Lintang Bhima, Sigid Kirana; Dhanardhono, Tuntas (RSUP Dr. Kariadi, 2023)
BACKGROUND: On February 19th, 2021, City of Semarang recorded 164 death cases of probable COVID-19. A study of patients who died from COVID-19 found that the death cases occured mostly in patients with comorbidities, such as hypertension, diabetes, heart disease, renal disease, chronic lung disease, and malignancy. The definitions of probable COVID-19 by WHO is a suspected case with radiological features leading to COVID-19 infection. AIMS: The purpose of this study was to prove pneumoniae, chronic lung disease, heart disease, hypertension, DM, renal disease, and malignancy as risk factors of mortality in probable COVID-19 patients. METHOD: This study used analytic observational design with cross-sectional study approach. Consecutive sampling technique was used with minimum sample of 57 probable COVID-19 medical records. The collected data was analyzed using the SPSS program with univariate, bivariate, and multivariate analysis. RESULT: The majority of probable COVID-19 patients died with a number of 65 subjects (91,5%), while the probable COVID-19 patients that survived are only 6 subjects (8,5%). Risk factors like pneumoniae (p=0,151; PR=0,9; 95%CI[0,78-1,03]), chronic lung disease (p=0,764; PR=1,09; 95%CI[1,02-1,18]), heart disease (p=0,591; PR=1,03; 95%CI[0,88-1.20]), hypertension (p=0,254; PR=1,08; 95%CI[0,95-1,23]), DM (p=0,361 PR=1,06; 95%CI[0,93-1,21]), renal disease (p=0,523; PR=1,10; 95%CI[1,02-1,19]), and malignancy (p=0,523; PR=1,10; 95%CI[1,02-1,19]) have not been proven to be risk factors for death in patients probable of COVID-19 at dr. Kariadi General Hospital, Semarang. CONCLUSION: Pneumoniae, chronic lung disease, heart disease, hypertension, diabetes mellitus, kidney disease, and malignancy have not been proven to be risk factors for death in patients probable of COVID-19 at dr. Kariadi General Hospital, Semarang.